2022
DOI: 10.48550/arxiv.2210.01369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Older Adults' Perceptions and Challenges in Using AI-enabled Everyday Technologies

Abstract: Artificial intelligence (AI)-enabled everyday technologies could help address age-related challenges like physical impairments and cognitive decline. While recent research studied older adults' experiences with specific AI-enabled products (e.g., conversational agents and assistive robots), it remains unknown how older adults perceive and experience current AI-enabled everyday technologies in general, which could impact their adoption of future AI-enabled products. We conducted a survey study (N=41) and semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…wearables) and can therefore collect large amounts of sensitive, personal data from patients in their own homes. A qualitative study of older people’s perception of AI technologies found data privacy to be a key concern, with older people feeling more vulnerable to privacy threats [ 49 ]. Older people with cognitive disorders or reduced technological literacy are particularly at risk [ 50 ].…”
Section: What Are the Challenges To Implementing Ai Technology In Hea...mentioning
confidence: 99%
“…wearables) and can therefore collect large amounts of sensitive, personal data from patients in their own homes. A qualitative study of older people’s perception of AI technologies found data privacy to be a key concern, with older people feeling more vulnerable to privacy threats [ 49 ]. Older people with cognitive disorders or reduced technological literacy are particularly at risk [ 50 ].…”
Section: What Are the Challenges To Implementing Ai Technology In Hea...mentioning
confidence: 99%